The (Globalized) Three Amigos: Translating and Disseminating HIV/AIDS Prevention Discourse - von Flotow, Luise (TTR)

(untitled) (Association canadienne de traductologie, 2005)
The effects of a translated text are notoriously hard to trace and establish. However, in the case of The Three Amigos, a series of short public service announcements on HIV/AIDS prevention that feature three comic figures (animated condoms) and accompany them through numerous adventures in 50 languages, the effects have been hugely successful–measurable in numbers of condoms sold! This article studies some of the translation problems posed by this Canadian production, and examines aspects of the Anglo-American source culture that are now hampering the distribution of this highly successful work. It thus positions translation dissemination as an issue related to source culture policies and politics that may play a bigger role in translation “effects” than a felicitous translation.Keywords: translating HIV/AIDS discourse, translating animation, translating wordplay and jokes, translation and source culture politics.